A kadmium és a pendimetalin toxikus interakciójának vizsgálata csirkeembrión - Szabó, Rita; Major, László; Lehel, József; Budai, Péter (GEORGIKON FOR AGRICULTURE, 2022)
The aim of this study was to determine the individual and combined toxic effects of STOMP 330 EC herbicide (330 g/l pendimethalin) and cadmium chloride on the development of chicken embryos. On the first day of incubation chicken eggs were injected by 0.1 ml of cadmium chloride solution (0.01%) and/or by 0.1 ml of STOMP 330 EC (1.25%). The chicken embryos were examined on day 19 by the followings: rate of embryo mortality, body weight, type of developmental anomalies. Body weight of the live embryos was evaluated with variance analysis, while RXC Chi2 test was used to statistically evaluate embryo mortality and developmental deformities. Our teratogenicity study revealed that the combined administration of cadmium chloride and pendimethalin containing herbicide formulation (STOMP 330 EC) caused a reduction in the body weight of embryos and increased the rate of embryonic mortality. The joint toxic effect of cadmium chloride and STOMP 330 EC is an additive effect compared to the individual toxicity of the test materials.
Keywords: cadmium chloride; STOMP 330 EC; chicken embryo; embryo mortality; joint toxic effect